A3_4 Speeding into the Future with Maglev Trains - Dickens, Cameron; Healings, Jack; Sampson, Elliot; Carlisle, Ben (Physics Special Topics, 2020)
In this paper we present our findings for the maximum theoretical speed of a maglev train. The maximum theoretical speed was calculated by finding the force acting on the train due to the magnets. Then using this in the equation for terminal velocity, where the weight is replaced by the magnetic force, the maximum velocity at sea level was found to be 280 ms−1 . Following this, we plotted a graph to show how the maximum velocity of the train would change at varying air densities. This graph shows that velocity rapidly increases as air density decreases.